Peranan Gereja Meningkatkan Derajat Kesehatan Jemaat - Siagian, Albiner (Sekolah Tinggi Diakones HKBP, 2022)
Health is one of the important things in this life. So for that, many people will keep their health, well. Besides it, they will do everything especially when they are sick through medical check-ups in abroad or another country even if they have to spend a lot of money. Actually, they are the best way to keep this health is grateful, give thanks to God for everything that He has done. It means that the church should help to be happy, hold and believe the Word of God.